N-Arylsulfonyl Hydrazones as Inhibitors of IMP-1 Metallo-β-Lactamase - Siemann, Stefan (American Society for Microbiology, 2002)
Members of a family of N-arylsulfonyl hydrazones have been identified as novel inhibitors of IMP-1, a metallo-β-lactamase of increasing prevalence. Structure-activity relationship studies have indicated a requirement for bulky aromatic substituents on each side of the sulfonyl hydrazone backbone for these compounds to serve as efficient inhibitors of IMP-1. Molecular modeling has provided insight into the structural basis for the anti-metallo-β-lactamase activity exhibited by this class of compounds.